Automated end-to-side anastomosis to the middle cerebral artery with C-Port xA: A feasibility study on human cadavers - Fontanella, Marco; Benevello, Chiara; Panciani, Pier; Ronchetti, Gabriele; Bacigaluppi, Susanna; Stefini, Roberto; Spena, Giannantonio; Garbossa, Diego; Ducati, Alessandro (Asian Journal of Neurosurgery, 2013)
Background: Anastomosis to the superficial temporal artery is suitable in patients with functional and structural impairment of the middle cerebral artery (i.e., complex aneurysms and skull base tumors), as either definitive treatment or an additional safety measure. A shorter occlusion time or a non-occlusive technique is expected to reduce the risk of cerebral ischemia following the procedure. In this cadaver study, we assessed the fitness of C-Port xA; device for use in superficial temporal artery (STA)-middle cerebral artery (MCA) bypass. Materials and Methods: Seven fixed human head specimens were prepared through eight pterional craniotomies. The superficial temporal artery was dissected and the sylvian fissure was opened to access the MCA. The C-Port xA was tested on each of the eight exposures. We recorded the lengths of both donor and recipient vessel, the durations of the procedure and the craniotomy, and sylvian scissure opening sizes. The bypass was then assessed by pressure injection of methylene blue in the donor vessel. Results: C-Port xA-assisted STA-MCA anastomosis was successfully accomplished in seven dissections. A minimum STA length of 7 cm, a sylvian scissure opening larger than 5 cm, and a craniotomy size of at least 6 × 6 cm appeared to be the requisites for a safe maneuverability of the device. The MCA occlusion time lasted in all cases less than 4.5 min, and we observed a clear improvement in time performance with growing experience. Conclusions: The results suggest that the C-Port xA device is suitable for STA-MCA bypass. We experienced a shorter occlusion time and a shorter learning curve compared to conventional techniques. Further miniaturization and special adaptation of this device may allow a future application even to deeper intracranial vessels. Clinical trials will have to assess the long-term results and benefits of this minimal occlusive technique.
Keywords: Automated end-to-side anastomosis; bypass; human cadavers; middle cerebral artery; superficial temporal artery